(untitled) (Marketing Journal, 2025)
This scientific article examines , from both theoretical and practical perspectives , the methodology for determining the level of trust in evaluation mechanisms within the higher education system and for calculating trust indicators . Within the scope of the study , the role of the concept of trust in the education system , approaches to measuring trust across different stakeholder groups , and a system of indicators formed through the integration of sociological and statistical methods are analyzed . It is substantiated that trust indices developed on the basis of an information -analytical approach contribute to enhancing the transparency and effectiveness of the evaluation system .